With a Little Help from my Enteric Microbial Friends - Berkhout, Ben (Frontiers in Medicine, 2015)
Although the disciplines of bacteriology and virology frequently come together in the setting of a diagnostic medical microbiology laboratory, the two scientific fields are usually miles apart. The microbiologists basically form two non-overlapping groups of scientists, the bacteriologists and virologists, which go to separate meetings and do not easily intermingle. Some recent research findings about elegant virus–bacterium interactions may change this situation. Obviously, interactions between these two microbes can occur only when they colocalize, which most likely occurs in the gut/intestines where 1014 commensal bacteria reside (the microbiota). We review findings on the following enteric microbial tandems: norovirus – Enterobacter cloacae, mouse mammary tumor virus (MMTV) – bacterial lipopolysaccharide (LPS), poliovirus and reovirus – intestinal bacteria. The close bacterium–virus interplay may also present options to develop unique therapeutic strategies for those infected, and to prevent further virus spread, and thus minimize the risk for the community.